Characterization of the Left-Sided Substrate in Arrhythmogenic Right Ventricular Cardiomyopathy. (December 2015) - Berte, Benjamin; Denis, Arnaud; Amraoui, Sana; Yamashita, Seigo; Komatsu, Yuki; Pillois, Xavier; Sacher, Frédéric; Mahida, Saagar; Wielandts, Jean-Yves; Sellal, Jean-Marc; Frontera, Antonio; Al Jefairi, Nora; et al.
Abstract : Background—: The correlates of left ventricular (LV) substrate in arrhythmogenic right ventricular (RV) cardiomyopathy are largely unknown. Methods and Results—: Thirty-two patients with arrhythmogenic RV cardiomyopathy (47±14 years; 6 women) were included. RV and LV dysplasia were defined from multidetector computed tomography and cardiac magnetic resonance imaging. Arrhythmias were characterized as right-sided or left-sided on 12-lead ECG recordings at baseline and during isoproterenol testing. In 14 patients, the imaging substrate was compared with voltage mapping and local abnormal ventricular activity. Imaging abnormalities were found in 32 (100%) and 21 (66%) patients on the RV and LV, respectively, intramyocardial fat on multidetector computed tomography being the most sensitive feature. LV involvement related to none of the Task Force criteria. Right-sided arrhythmias were more frequent than left-sided arrhythmias ( P =0.003) although the latter were more frequent in case of LV involvement ( P =0.02). The agreement between low voltage and fat on multidetector computed tomography was high on the RV when using either endocardial unipolar or epicardial bipolar data (κ=0.82 and κ=0.78, respectively) but lower on the LV (κ=0.54 for epicardial bipolar). LV local abnormal ventricular activity was found in all patients with LV involvement, and none of the others. The density of local abnormal ventricular activity within fat areas was similar between the RV and LV ( P =0.57). Conclusions—: LV substrate is frequent in arrhythmogenic RV cardiomyopathy, but poorly identified by current diagnostic strategies. Left-sided arrhythmias are more frequent in case of LV involvement. LV fat hosts the same density of local abnormal ventricular activity as RV fat, but is less efficiently detected by voltage mapping. These results support the need for alternative diagnostic strategies to identify LV dysplasia.